The effects of metacognitive hints on problem solving (the case of the nine-dot problem) - O.A. Chugunova; N.I. Loginov (Экспериментальная психология)
Context and relevance. Metacognitive hints as a type of influence on problem solving have been used in research relatively recently. And at present the specifics of their influence on solving nine-dot problem have not been sufficiently studied. Objective. To identify the influence of metacognitive hints on the process of solving nine-dot problem. Hypothesis. The metacognitive hints presented before solving the task increase the frequency of monitoring and control of one's own thinking processes and positively affect the effectiveness of solving nine-dot problem. Methods and materials. The study involved 60 participants (M = 20.5, SD = 1.6, 70% female), divided into two equal groups: with metacognitive hints (experimental group) and without metacognitive hints (control group). The process of solving nine-dot problem was studied using the method of thinking aloud and subsequent analysis of verbal reports. Results. The participants of the experimental group were significantly more likely to monitor and control their own thought processes, which was manifested in an increase in the number of statements about their own solving process. At the same time no significant differences were found between the participants of the experimental and control groups in terms of the success of solving nine-dot problem. Conclusions. The study has been shown that metacognitive hints increase the number of metacognitive operations, which is reflected in verbalization, but at the same time do not increase the success of solving nine-dot problem.